Nomenclatorial novelties of the genus Leucania Ochsenheimer, 1816 that occur in Central America (Lepidoptera: Noctuidae) - Morton S. Adams; Timothy L. McCabe (SHILAP)
We treat five species of Leucania Ochsenheimer, 1816 originally described in Cirphis Walker, [1865, p. 623] by Draudt (1924), whose name-bearing types were destroyed in the bombing during World War II. These species are Cirphis biforis Draudt, 1924, C. macellaria Draudt, 1924, C. clara Draudt, 1924, C. opalisans Draudt, 1924, and C. carnea Draudt, 1924. We make the latter three species objective synonyms of Leucania multipunctata Druce, 1889. A neotype is designated for Cirphis biforis Draudt, 1924 and its original description is provided. Cirphis macellaria is recognized as a subjective synonym of L. clarescens Möschler, 1890. A total of eleven synonyms are proposed: four Draudt objective synonyms and seven additional synonymies for Central American Leucania species. Lectotypes are designated for Cirphis pyrastis Hampson, 1905 and C. seteci Dyar, 1914. Illustrations of the imago, valvae, everted endophallus, and bursa copulatrix are provided for L. biforis (Draudt, 1924), L. multipunctata Druce, 1889, L. pyrastis (Hampson, 1905), and L. sarcistis (Hampson, 1905). Photographs of the types of L. extenuata Guenée, 1852 and L. infatuans are provides. New character states of the forewing and genitalia are described. A list of nomenclatorial changes is provided.